Selenium improves the content of vitamin C in the fruit of strawberry by regulating the enzymes responsible for vitamin C metabolism - Ninghai Lu; Limin Wu; Xiaoqing Zhang; Yanyan Zhang; Changjuan Shan (Plant, Soil and Environment, 2022)
To investigate how sodium selenite (Na2SeO3) regulated the content of vitamin C (Vc) in strawberry fruit, we explored the effects of Na2SeO3 on the enzymes responsible for Vc metabolism. The findings showed that 10 mg/L Na2SeO3 improved the activities of ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), glutathione reductase (GR), l-galactono-1,4-lactone dehydrogenase (GalLDH) at periods of young fruit (YFP), small fruit (SFP), middle fruit (MFP), large fruit (LFP), white fruit (WFP), colour-changed fruit (CFP) and ripen fruit (RFP). 30 mg/L Na2SeO3 improved the activities of APX, MDHAR, GR and GaILDH at YFP, LFP, WFP, CFP and RFP. 60 mg/L Na2SeO3 improved the activities of MDHAR, GR and GaILDH at all periods studied. In addition, 10 mg/L Na2SeO3 decreased the activity of ascorbate oxidase (AAO) at WFP and CFP. 30 mg/L Na2SeO3 decreased AAO activity at MFP, LFP, WFP and CFP. 60 mg/L Na2SeO3 decreased AAO activity at YFP, SFP, MFP, LFP, WFP and CFP. Meanwhile, all concentrations of Na2SeO3 significantly increased the contents of Vc and Se. Among different concentrations, 30 mg/L Na2SeO3 had better effects on the enzymes responsible for Vc metabolism, which further improved Vc content in strawberry fruit. Besides, all concentrations of Na2SeO3 increased fruit average weight, number of fruits per plant and fruit yield, compared with control. The above results indicated that Na2SeO3 could improve the content of Vc in fruit and fruit yield of strawberries, especially for 30 mg/L Na2SeO3.